A Case Study of Conflicts Between Students in the Department of Family Welfare Education, Faculty of Engineering, Universitas Negeri Manado - Sumolang, Nortje (International Journal of Information Technology and Education, 2024)
This research focuses on students of the gastronomy, tourism/hospitality, and fashion design study program of the Faculty of Engineering, Manado State University, in the odd semester of the 2015/2016 academic year. The students selected in this study are 48 people. This study uses qualitative research. The data collection techniques used are (1) Observation, (2) Interview, (3) Documentation study, and (4) a combination of the three (triangular). The research instruments are the researcher himself, a field notebook, and equipped with an interview guide. The data obtained was then analyzed by the following steps: (1) coding, (2) data reduction, (3) data recitation, and (4) data verification. Furthermore, the validity of the data is carried out with the following steps: (a) Credibility, (b) transferability, and (c) dependability. From the results of the research obtained by the researcher through interviews with 48 students, the conflicts that occurred between students and students (individual conflicts) in the Department of Family Welfare Education of the Department of Culinary Arts, Tourism/Hospitality, and Fashion Study Program at Manado State University were caused by: (1) borrowing money was not returned (2) borrowed books were not returned (3) differences of opinion in group discussions (4) group assignments were entered late (5) there was no cooperation in making group assignments and the last sequence (6) of money theft. Based on the students' findings, the researcher interviewed lecturers of the PKK Department of the Gastronomy, tourism/hospitality, and fashion study program of the Faculty of Engineering, State University of Manado, and almost all lecturers supported the students' statements. The strategies used by the head of the PKK department in managing conflicts include: (a) the head of the department gives trust to the head of the level in resolving individual conflicts, (b) if this case cannot be resolved by the head of the level, then the head of the department takes over the case using a problem-solving approach.